2017
DOI: 10.1186/s12955-017-0686-9
|View full text |Cite
|
Sign up to set email alerts
|

Dietary habits, oral impact on daily performance and type 2 diabetes: a matched case-control study from Sudan

Abstract: BackgroundIt is evident that social and behavioural factors influence on individuals’ general health and quality of life. Nevertheless, information about the influence of dietary habits on oral health-related quality of life is limited; especially among patients with type 2 diabetes (T2D). The aim of this study was to examine the influence of dietary habits and clinical oral health indicators on oral health-related quality of life in individuals with and without T2D.MethodsA total of 149 T2D cases and 298 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 38 publications
1
11
1
Order By: Relevance
“…Population‐based studies have shown that prevalence of oral impacts on the quality of life of older people ranged between 14% and 57.8% worldwide . Other less representative cross‐sectional studies have found prevalence of OIDP ranging between 57.9% and 92.7% . Of these studies, few considered the impact of characteristics other than clinical oral status on OIDP .…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…Population‐based studies have shown that prevalence of oral impacts on the quality of life of older people ranged between 14% and 57.8% worldwide . Other less representative cross‐sectional studies have found prevalence of OIDP ranging between 57.9% and 92.7% . Of these studies, few considered the impact of characteristics other than clinical oral status on OIDP .…”
Section: Discussionmentioning
confidence: 85%
“…8,12,14,16 Other less representative cross-sectional studies have found prevalence of OIDP ranging between 57.9% and 92.7%. 7,9,13,15 Of these studies, few considered the impact of characteristics other than clinical oral status on OIDP. 12,14,16 This study has shown that prevalence of oral impacts on the quality of life of older people was defined by their clinical oral status and by means of contextual socio-economic and individual socio-demographic characteristics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The majority of the studies used a cross-sectional design (86%). Only 4 studies (6%) [21,66,79,115] reported longitudinal data and 6% were case-control studies [16,61,116,117]. More studies were conducted in urban areas (41%) compared to rural areas (21%), with 33% of studies conducted in both geographical areas.…”
Section: Descriptivementioning
confidence: 99%